Clinical Proteomics Profiling for Biomarker Identification Among Patients Suffering With Indian Post Kala Azar Dermal Leishmaniasis - Jaiswal, Priyank; Ghosh, Manab; Patra, Goutam; Saha, Bibhuti; Mukhopadhyay, Sumi (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Post Kala Azar Dermal Leishmaniasis (PKDL) is a non-fatal dermal sequel of Visceral Leishmaniasis (VL), affecting individuals worldwide. Available diagnostic tools lack sensitivity and specificity towards identifying macular (MAC) PKDL patients, due to low parasite load in patients’ sample. Confirmatory test like punch biopsy are invasive and painful. In contrast, the highly sensitive qPCR based diagnostic method is costly and requires high expertise. Considering the rural nature of this disease and the prevailing situation of diagnostic scenario, PKDL patients mostly remains unattended from receiving proper medical care. They in turn act as “mobile parasite reservoir”, responsible for VL transmission among healthy individuals (HI). This study aims to identify PKDL disease specific glycated protein biomarkers to efficiently distinguish MAC and POLY PKDL patients from disease control individuals. Methodology: Previously our lab had identified importance of glycated (Circulating Immune Complexes) CICs, among PKDL patients. This study aims to further characterize disease specific glycated protein biomarkers, among MAC PKDL patients for both diagnostic and prognostic evaluation of the disease. LC-MS/MS based comparative spectral count analysis of MAC PKDL to polymorphic (POLY) PKDL, HI and Cured (CR) individuals were performed. Proteins level alterations among all study groups were confirmed by Western blot and Enzyme-linked Immuno Sorbant Assay (ELISA). Results: Among MAC PKDL patients 43, 60, 90 proteins were altered compared to POLY PKDL, HI and CR groups respectively. Filtering for the most significant proteins, Plasminogen (PLG) and Vitronectin (VTN) were identified which promisingly identified MAC PKDL cases. Active surveillance results from endemic districts of West Bengal revealed drastic rise of MAC PKDL cases, alarming the urgency for field adaptive efficient biomarker. Conclusion: This current study aims to establish PLG and VTN as novel diagnostic and prognostic protein biomarker for MAC and POLY PKDL cases management.